Kepastian Hukum Hak Informasi: Problematika Konsumen dan Rahasia Dagang - A Cery Kurnia; Reko Dwi Salfutra; Syam Dwi Hanafiah (Fakultas Hukum Universitas Bangka Belitung, 2022)
This research is a juridical study of the information rights contained in teh Act Number 8 of 1999 of years and the Act Number 30 of 2020 of years. Within the regulatory framework regarding the right to information on a product, it is a legal issue that has caused a lot of polemic in the business sector. One side, consumers have the right to obtain correct, clear and honest information on any goods/services purchased, and the other side, business actors also have the right to close information on goods/services sold on the grounds that they are protected by trade secrets. This research was conducted using a normative juridical method with conceptual approach and normative approach. This research proved, that there is a conflict of norms regarding the regulation of information rights between The Act Number 30 of 2000 of years and the Act Number 8 of 1999 of years, so that the regulation of information rights does not bring a legal certainty. Therefore, it is necessary to synchronize the arranggement on the regulation of information rights between The Act Number 30 of 2000 of years and the Act Number 8 of 1999 of years.